Observations on a severe epidemic of influenza at Senekal O.F.S. South Africa during 1918-1919: with special reference to prophylaxis and treatment - Fouche, F. P. (The University of Edinburgh, 1921)
Many therapeutic measures have been recommended, and many ranked as of great value, if not actually specific, in this disease. No one remedy has however, attained anything approaching universal recognition.

In this Thesis I will endeavour to show::- Firstly, the beneficial effects derived from the use of a Polyvalent vaccine, both Prophylactically and as treatment during an attack.

Secondly, to demonstrate the great Therapeutic value of Vene-section in certain conditions.